2006
DOI: 10.1111/j.1365-2893.2006.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of pre‐S mutations in patients with genotype C hepatitis B virus infection

Abstract: We investigated the overall and site-specific prevalence of pre-S mutations and its clinical significance in patients with genotype C hepatitis B virus (HBV) infection. Three hundred subjects were included: 50 asymptomatic carriers (AC), 87 chronic hepatitis (CH), 91 liver cirrhosis (LC) and 72 hepatocellular carcinoma (HCC). Pre-S mutations were determined by nucleotide sequence analysis. Possible correlations between pre-S mutations and clinical/virological parameters were examined. Pre-S mutations were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
77
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 35 publications
14
77
1
Order By: Relevance
“…HBV variants with pre-S deletions were identified in both liver explant and blood samples. In general, these variants are often observed in patients with advanced disease, such as liver cirrhosis and HCC (12,13). This is consistent with the findings of this study, as the subject evaluated here had end-stage liver disease prior to a liver transplantation.…”
Section: Novel Spliced Variantssupporting
confidence: 82%
See 1 more Smart Citation
“…HBV variants with pre-S deletions were identified in both liver explant and blood samples. In general, these variants are often observed in patients with advanced disease, such as liver cirrhosis and HCC (12,13). This is consistent with the findings of this study, as the subject evaluated here had end-stage liver disease prior to a liver transplantation.…”
Section: Novel Spliced Variantssupporting
confidence: 82%
“…The mRNAs of these envelope proteins are transcribed from a single ORF; however, each has its own initiation codon (11). In general, the number of pre-S mutations can increase during the progression of CHB (12), and pre-S mutations are more prevalent in patients with HCC and liver cirrhosis (13). It has also been shown that NA treatments can select viral variants whose genomes encode truncated surface proteins, which could, in turn, accelerate liver disease progression (14).…”
mentioning
confidence: 99%
“…Our study showed a significantly higher rate of pre-S2 deletions in the children of the HCC group than in the group with chronic HBV infection. The meaning of our results is unique and not merely in agreement with the studies in adults, because we found that pre-S2 deletions in HBV genomes did not necessarily take decades to accumulate, as in adult patients with advanced liver diseases (1,(15)(16)(17)(18)(19)(20)(21)(22); they emerged in nearly half of the young children with HBV-related HCC that developed in a relatively short period of time.…”
Section: Discussionsupporting
confidence: 68%
“…Previous data also demonstrated that T1753A/G/C mutations occurred later than the double BCP mutations in the natural course of chronic HBV infection (Takahashi et al, 1999). Regarding pre-S deletion, it has been shown in several reports that such mutant is an important risk factor of HCC (Chen et al, 2006;Choi et al, 2007). In vitro studies have also showed that intracellular accumulation of pre-S mutant proteins can modify HBV protein expression, induce ER stress and increased DNA damage (Hsieh et al, 2004).…”
Section: Discussionmentioning
confidence: 97%